Noise suppression of infrared thermal imaging of rocket exhaust plume using SPOD - Fu, Debin; Sun, Ao; Niu, Qinglin (Frontiers in Physics, 2024)
The quality of infrared thermal imaging will decrease due to the presence of environmental noise. In this study, the noise data of the unsteady rocket exhaust plume flow field was simulated using Gaussian white noise, and the infrared thermal image of the plume was numerically calculated using the narrow band method (SNB) and the line of sight (LOS) method. The denoising of infrared thermal imaging was achieved through the spectral proper orthogonal decomposition (SPOD) inversion method. The research results indicate that Gaussian white noise leads to larger infrared thermal image residuals in the plume intrinsic region compared to the mixed region. The infrared thermal image in the 2.7 μm band is greatly affected by noise with an average error of 21.1%, while the average error in the 4.3 μm band is 17.6%. After SPOD denoising, the error of the plume infrared thermal image is reduced by more than 50%.